Use of Whole-Genome Sequencing in the Investigation of a Nosocomial Influenza Virus Outbreak. (5th June 2018) - Houlihan, Catherine F; Frampton, Dan; Ferns, R Bridget; Raffle, Jade; Grant, Paul; Reidy, Myriam; Hail, Leila; Thomson, Kirsty; Mattes, Frank; Kozlakidis, Zisis; Pillay, Deenan; Hayward, Andrew; et al.
Abstract: Traditional epidemiological investigation of nosocomial transmission of influenza involves the identification of patients who have the same influenza virus type and who have overlapped in time and place. This method may misidentify transmission where it has not occurred or miss transmission when it has. We used influenza virus whole-genome sequencing (WGS) to investigate an outbreak of influenza A virus infection in a hematology/oncology ward and identified 2 separate introductions, one of which resulted in 5 additional infections and 79 bed-days lost. Results from WGS are becoming rapidly available and may supplement traditional infection control procedures in the investigation and management of nosocomial outbreaks. Abstract : Influenza virus whole-genome sequencing (WGS) was used to investigate an outbreak of influenza A virus infection in a hematology/oncology ward; 2 separate introductions were identified. The role of WGS for nosocomial outbreak investigation is discussed.